Palladium-catalyzed picolinamide-directed iodination of remote ortho-C−H bonds of arenes: Synthesis of tetrahydroquinolines - Nack, William A.; Wang, Xinmou; Wang, Bo; He, Gang; Chen, Gong (Beilstein Journal of Organic Chemistry, 2016)
A new palladium-catalyzed picolinamide (PA)-directed ortho-iodination reaction of ε-C(sp2)−H bonds of γ-arylpropylamine substrates is reported. This reaction proceeds selectively with a variety of γ-arylpropylamines bearing strongly electron-donating or withdrawing substituents, complementing our previously reported PA-directed electrophilic aromatic substitution approach to this transformation. As demonstrated herein, a three step sequence of Pd-catalyzed γ-C(sp3)−H arylation, Pd-catalyzed ε-C(sp2)−H iodination, and Cu-catalyzed C−N cyclization enables a streamlined synthesis of tetrahydroquinolines bearing diverse substitution patterns.
Keywords: iodination; palladium; remote C–H activation; tetrahydroquinoline

(untitled) - Katritzky, A. R.; Rachwal, S.; Rachwal, B. (Tetrahedron, 1996)

(untitled) - Sridharan, V.; Suryavanshi, P. A.; Menéndez, J. C. (Chem. Rev., 2011)

(untitled) - Akiyama, T.; Morita, H.; Fuchibe, K. (J. Am. Chem. Soc., 2006)

(untitled) - Liu, H.; Dagousset, G.; Masson, G.; Retailleau, P.; Zhu, J. (J. Am. Chem. Soc., 2009)

(untitled) - Han, Z.-Y.; Xiao, H.; Chen, X.-H.; Gong, L.-Z. (J. Am. Chem. Soc., 2009)

(untitled) - Rousseaux, S.; Liégault, B.; Fagnou, K. (Chem. Sci., 2012)

(untitled) - Saget, T.; Cramer, N. (Angew. Chem., Int. Ed., 2012)

(untitled) - Nack, W. A.; He, G.; Zhang, S.-Y.; Chen, G. (Org. Lett., 2013)

(untitled) - Zaitsev, V. G.; Shabashov, D.; Daugulis, O. (J. Am. Chem. Soc., 2005)

(untitled) - Nadres, E. T.; Daugulis, O. (J. Am. Chem. Soc., 2012)

(untitled) - Nadres, E. T.; Santos, G. I. F.; Shabashov, D.; Daugulis, O. (J. Org. Chem., 2013)

(untitled) - He, G.; Chen, G. (Angew. Chem., Int. Ed., 2011)

(untitled) - Zhao, Y.; Chen, G. (Org. Lett., 2011)

(untitled) - He, G.; Zhao, Y.; Zhang, S.; Lu, C.; Chen, G. (J. Am. Chem. Soc., 2012)

(untitled) - Zhang, S.-Y.; He, G.; Zhao, Y.; Wright, K.; Nack, W. A.; Chen, G. (J. Am. Chem. Soc., 2012)

(untitled) - He, G.; Lu, C.; Zhao, Y.; Nack, W. A.; Chen, G. (Org. Lett., 2012)

(untitled) - Zhao, Y.; He, G.; Nack, W. A.; Chen, G. (Org. Lett., 2012)

(untitled) - Zhang, S.-Y.; He, G.; Nack, W. A.; Zhao, Y.; Li, Q.; Chen, G. (J. Am. Chem. Soc., 2013)

(untitled) - Roman, D. S.; Charette, A. B. (Org. Lett., 2013)

(untitled) - Huang, L.; Li, Q.; Wang, C.; Qi, C. (J. Org. Chem., 2013)

(untitled) - Barluenga, J.; Álvarez-Gutiérrez, J. M.; Ballesteros, A.; González, J. M. (Angew. Chem., Int. Ed., 2007)

(untitled) - Espuña, G.; Arsequell, G.; Valencia, G.; Barluenga, J.; Álvarez-Gutiérrez, J. M.; Ballesteros, A.; González, J. M. (Angew. Chem., Int. Ed., 2004)

(untitled) - Lu, C.; Zhang, S.-Y.; He, G.; Nack, W. A.; Chen, G. (Tetrahedron, 2014)
See for our recent report on Pd-catalyzed PA-directed ortho C−H halogenation of benzylamine substrates.

(untitled) - Kalyani, D.; Dick, A. R.; Anani, W. Q.; Sanford, M. S. (Tetrahedron, 2006)

(untitled) - Wan, X.; Ma, Z.; Li, B.; Zhang, K.; Cao, S.; Zhang, S.; Shi, Z. (J. Am. Chem. Soc., 2006)

(untitled) - Mei, T.-S.; Giri, R.; Maugel, N.; Yu, J.-Q. (Angew. Chem., Int. Ed., 2008)

(untitled) - Mo, F.; Yan, J. M.; Qiu, D.; Li, F.; Zhang, Y.; Wang, J. (Angew. Chem., Int. Ed., 2010)

(untitled) - Schröder, N.; Wencel-Delord, J.; Glorius, F. (J. Am. Chem. Soc., 2012)

(untitled) - Hennings, D. D.; Iwasa, S.; Rawal, V. H. (J. Org. Chem., 1997)

(untitled) - Leblanc, M.; Fagnou, K. (Org. Lett., 2005)

(untitled) - Li, J.-J.; Giri, R.; Yu, J.-Q. (Tetrahedron, 2008)

(untitled) - Leow, D.; Li, G.; Mei, T.-S.; Yu, J.-Q. (Nature, 2012)

(untitled) - Li, J.-J.; Mei, T.-S.; Yu, J.-Q. (Angew. Chem., Int. Ed., 2008)

(untitled) - Chen, X.; Engle, K. M.; Wang, D.-H.; Yu, J.-Q. (Angew. Chem., Int. Ed., 2009)

(untitled) - Lyons, T. W.; Sanford, M. S. (Chem. Rev., 2010)

(untitled) - Zhang, X.-G.; Dai, H.-X.; Wasa, M.; Yu, J.-Q. (J. Am. Chem. Soc., 2012)
Alkali cations (e.g., Na+, K+) might play a useful role in this PA-directed C–H functionalization reaction. See for mechanistic investigations on related reaction systems.

(untitled) - Ano, Y.; Tobisu, M.; Chatani, N. (J. Am. Chem. Soc., 2011)

(untitled) - Ault, A. (J. Chem. Educ., 1966)

(untitled) - Rosenthal, J.; Schuster, D. I. (J. Chem. Educ., 2003)

(untitled) - Thansandote, P.; Lautens, M. (Chem. – Eur. J., 2009)

(untitled) - Mei, T.-S.; Kou, L.; Ma, S.; Engle, K. M.; Yu, J.-Q. (Synthesis, 2012)

(untitled) - Nack, W. A.; Chen, G. (Synlett, 2015)